Evaluasi Prosedur Pembayaran Hutang Kepada Vendor Oleh Account Payable di Departemen Accounting Grand Kangen Hotel Evaluation of Procedures for Paying Debts to Vendors by Account Payable in the Accounting Department Grand Kangen Hotel - Rinreswara, Febrinda Rohadi; Kuntari, Erlina Daru; Handayani, Lutfi; Erryawan, Ervin (EBBANK, 2024)
This project research conducted in the accounting department aims to explain the procedures for paying debts to vendors carried out by account payables in the accounting department of the Grand Kangen Hotel. Evaluate whether the hotel debt payment procedure is effective and efficient or not. The method of preparing this final project is to use a descriptive qualitative research method with data collection tools in the form of observation and documentation.The results project research of the payment procedure begins with checking the amount of hotel debt by the account payable in the hotel software system. Then the vendor comes to the hotel to exchange invoices, then the account payable checks the form. Followed by adjusting the amount of hotel debt between the vendor data and the hotel software system. Files are collected and submitted to the chief accounting and general manager. Account payable prints application files and writes bank transfer slips for debt payments. Then it is sent to the finance director for approval. Then go to the bank to make a transfer transaction for payment of debt. Official slip after successful bank transaction sent to vendor. Next is the procedure for paying debts to vendors, nine steps are considered effective, and three steps are ineffective. But on the implementation of the three steps results can be achieved by accounts payable. So the evaluation of procedures for paying debts to vendors by account payable is determined to be effective. The eight-step procedure for paying debts to vendors was evaluated as an efficient step, and only four steps were inefficient. But the implementation of the four steps benefited and was successfully carried out by the account payable. So the evaluation of debt payment procedures to vendors carried out by accounts payable is determined to be efficient.